A rare case of eczema herpeticum associated with HIV: A case report. (2023) - Chourasia, Prabal; Bernstein, Norman D.; Ajmera, Kunal M.; Pandit, Trupti; Pandit, Ramesh; Goyal, Lokesh
Abstract: Eczema herpeticum (EH), also known as Kaposi's varicelliform eruption, is a disseminated herpes simplex virus infection seen in patients with underlying skin conditions, most commonly atopic dermatitis. Monomorphic vesicles and "punched-out" erosions with hemorrhagic crusts over eczematous regions are the hallmarks of EH's presentation. Here, we discuss a first reported case of eczema herpeticum in a patient living with well controlled HIV with prior steroid use. A 30-year-old male patient living with HIV presented to the hospital with a generalized rash involving the face, neck, arms, hands, low back region, and both feet. Herpes simplex 1 and 2 by PCR DNA were detected from external auditory ear canal drainage. The patient was treated with intravenous acyclovir and responded well. He had long term history of eczema and required acyclovir prophylaxis later.